2001
DOI: 10.1136/ijgc-00009577-200107000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian fibrosarcoma with long-term survival: A case report

Abstract: Abstract.Huang Y-C, Hsu K-F, Chou C-Y, Dai Y-C, Tzeng C-C. Ovarian fibrosarcoma with long-term survival.Primary ovarian fibrosarcoma is an exceedingly rare malignant ovarian stromal tumor which has a poor prognosis. We report here a 46-year-old woman who suffered from irregular vaginal bleeding for 2 months. She received hysterectomy and salpingo-oophorectomy due to a provisional diagnosis of uterine and ovarian tumors. At surgery, an 8-cm ovarian solid multilobular tumor was found. Frozen section examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…In 1997, Tsuji et al established that the MIB‐1 (Ki‐67) labeling index and proliferative index by DNA flow cytometry, which were higher in fibrosarcomas, could also be used in the differential diagnosis especially in cases with 3–4 mitotic figures/hpf (8) . This finding has also been confirmed in some other recent reports (3,13,15) . Tsuji et al (8) also concluded that trisomy 8 cells in the tumor may be a reliable marker for diagnosis of fibrosarcomas; this has not yet been confirmed by other reports.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In 1997, Tsuji et al established that the MIB‐1 (Ki‐67) labeling index and proliferative index by DNA flow cytometry, which were higher in fibrosarcomas, could also be used in the differential diagnosis especially in cases with 3–4 mitotic figures/hpf (8) . This finding has also been confirmed in some other recent reports (3,13,15) . Tsuji et al (8) also concluded that trisomy 8 cells in the tumor may be a reliable marker for diagnosis of fibrosarcomas; this has not yet been confirmed by other reports.…”
Section: Discussionsupporting
confidence: 51%
“…Primary ovarian sarcomas are very rare tumors and account for less than 3% of all ovarian neoplasias. Among the primary ovarian sarcomas, fibrosarcomas are relatively common (1,3) . However, there are only about 30 cases in the literature reported within past three decades, showing the extreme rarity of these tumors (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian fibrosarcoma is a rare and aggressive disease with poor prognosis despite radical surgery and adjuvant therapy 1–4 …”
Section: Discussionmentioning
confidence: 99%
“…Currently, the treatments and prognostic factors of ovarian brosarcoma are still under discussion. Although there have been several reported cases with long survival [14,15], the prognosis of ovarian brosarcoma is still generally poor.…”
Section: Prognosismentioning
confidence: 99%